INDIVIDUALIZED TREATMENT FOR POSTHYSTERECTOMY VAGINAL EVERSION – CASE REPORT AND LITERATURE REVIEW - Pantović, Sveto; Dotlić, Jelena; Stefanović, Katarina; Milošević, Branislav; Pantović, Kosta; Likić Lađević, Ivana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Currently, there are different recommendations for obtaining optimal treatment of vaginal eversion. The presented case highlights current options for individualized treatment of complete vaginal eversion. Case report: A 61-year-old woman presented with complete vaginal eversion stage IV seventeen years after classic abdominal hysterectomy with bilateral adnexectomy. For anterior compartment prolapse, it was decided to perform anterior colpoplasty and bladder elevation using U sutures, while Nichols bilateral sacrospinal fixation was the chosen technique for correction of the rectocele/enterocele and prolapse of the posterior vaginal wall. The postoperative course was uneventful, and the resolution of vaginal eversion was confirmed on a six-month check-up. Conclusions: The surgical repair incorporating anterior colpoplasty combined with bilateral sacrospinous ligament fixation is advised for the advanced stage of complex vaginal eversions. This treatment option is an effective and safe technique.